Application of Differentiated Learning to Increase Student Learning Motivation - Hayati, Fadhilah; Wanahari, Maulidia; Siregar, Noveranza Habiyanti Said; Dewi, Sri Rahmah; Gunarto, Bayu (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
Differentiated Learning is applied in the Free Curriculum with a focus on students to meet their learning needs. This learning encompasses four approaches: content, process, product, and learning environment. Differential learning is an effort to meet student learning needs by creating diverse classrooms and providing access to learning resources as well as new ideas, aimed at improving student learning outcomes. Includes a number of cycles, each consisting of planning, implementation and observation, and reflection. These stages continue repeatedly until the purpose of the investigation is achieved. The action is to use differential learning methods. From the comparisons presented, it is seen that there is a significant improvement in student learning outcomes on magnetic material through the application of differential learning. In the pre-cycle phase, the presentation of students who have graduated increased from 43.75% to 90.62% in the second cycle. This shows that the application of differentiation strategies has successfully improved students' achievements in understanding the material. The success of improving student learning outcomes through differential learning in class X-2 SMA Negeri 2 Kisaran is determined by several factors, both internal and external. Internal factors include student intelligence, interests, and motivation.